Clinical and school-based intervention strategies for youth obesity prevention: A systematic review - Caron, Théo; Bernard, Paquito; Gadais, Tegwen (Frontiers in Sports and Active Living, 2023)
In the last couple of decades, numerous intervention strategies (IS) have been set up in school/community or clinical sectors using physical activity (PA) in order to prevent youth obesity. Those two sectors have shown interesting elements in terms of efficient results and best practices mechanisms, but they have been rarely compared to learn one from the other. The aim of the systematic review was to analyze and synthesize PA IS from school/community or clinical domains, for the period 2013–2017, in French or English, targeting youths 5–19 years old through primary, secondary and tertiary prevention. In total, 68 full articles were kept for data extraction and synthesis and 617 were excluded because they did not meet eligibility criteria (61 of 68 were kept for the final analysis). Results identified a number of differences between the studies of the various IS sectors and identified a third type of IS: mixed sectors. Mixed IS (clinical and school-community) should be privileged because it can benefit from both IS: school/community-based and clinical-based strengths. Mixed IS showed the most promising results. This review also showed differences between sectors and their IS on intervention teams, prevention objectives, duration, material and efficiency. Future studies should focus on establishing a prevention program in a given geographical area involving all stakeholders with their respective skills/knowledge, in decision-making and in the development of the IS, to ensure the program is the most efficient and best adapted to its environment.